2003
DOI: 10.1080/10635150309311
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Bootstrap and Posterior Probability Values in the Four-Taxon Case

Abstract: Assessment of the reliability of a given phylogenetic hypothesis is an important step in phylogenetic analysis. Historically, the nonparametric bootstrap procedure has been the most frequently used method for assessing the support for specific phylogenetic relationships. The recent employment of Bayesian methods for phylogenetic inference problems has resulted in clade support being expressed in terms of posterior probabilities. We used simulated data and the four-taxon case to explore the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 15 publications
4
46
0
2
Order By: Relevance
“…The ML topology shows two major groups, one supported by maximum likelihood bootstrap (MLB = 92) and by Bayesian posterior probabilities (BPP = 0.99; clade A), and a second clade not supported by maximum likelihood bootstrap (MLB = 47) but supported by Bayesian posterior probabilities (BPP = 0.96; clade B). The difference in the support for the clade B may result from a variety of causes, including the different nature of both analyses and overestimation of posterior probabilities [52][53][54][55]. The two sequences of L. uniformis were placed in a supported clade (MLB = 100, BPP = 1.0) within the L. nigroviridis group, related (but unsupported) to the supported clade that included samples from La Campana, El Roble, and Chicauma (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ML topology shows two major groups, one supported by maximum likelihood bootstrap (MLB = 92) and by Bayesian posterior probabilities (BPP = 0.99; clade A), and a second clade not supported by maximum likelihood bootstrap (MLB = 47) but supported by Bayesian posterior probabilities (BPP = 0.96; clade B). The difference in the support for the clade B may result from a variety of causes, including the different nature of both analyses and overestimation of posterior probabilities [52][53][54][55]. The two sequences of L. uniformis were placed in a supported clade (MLB = 100, BPP = 1.0) within the L. nigroviridis group, related (but unsupported) to the supported clade that included samples from La Campana, El Roble, and Chicauma (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of the recovered clades some are only supported by PP values. It has already been shown that Bayesian statistics can overestimate support for particular nodes on a tree (Cummings & al., 2003;Simmons & al., 2004). On the other hand, it has been reported that Bayesian analysis can provide high support values for correct clades with fewer characters than needed for bootstrap (Alfaro & al., 2003).…”
Section: Continued Top Rightmentioning
confidence: 99%
“…A consensus tree was made from the remaining samples. Because posterior probabilities-the support values used by bayesian analysis to indicate confidence in groups-have been criticized 29 , we also used bootstrapping to provide an additional indication of support for relationships. Each data set was bootstrapped (100 replicates) and used to make distance matrices under the same evolutionary model as in the bayesian analysis, using custom (P4) software (available on request).…”
Section: Phylogenetic Analysismentioning
confidence: 99%